Gastrointestinal Surgery and Related Complications in Patients with Ehlers-Danlos Syndrome: A Systematic Review - Burcharth, Jakob; Rosenberg, Jacob (Digestive surgery, 2012)
Introduction: Ehlers-Danlos syndrome (EDS) is a rare inherited group of connective tissue diseases characterized by joint hypermobility, skin hyperextensibility and bruising tendency. Common features of patients with EDS include vascular and gastrointestinal perforations. The purpose of this systematic review is to address gastrointestinal diseases and the complications associated with surgical treatment of diseases relating to the gastrointestinal system in patients with EDS. Methods: PubMed search including the Medical Subject Heading (MeSH) terms ‘Ehlers-Danlos Syndrome’ and ‘Gastrointestinal Diseases’, and an Embase search including the Map Term to Subject Heading ‘Ehlers-Danlos Syndrome’ with ‘AND’ function of the keyword ‘Gastrointestinal’. Results: The literature search resulted in inclusion of 53 articles after application of eligibility criteria. The primary results drawn from the literature was that spontaneous ruptures of vessels and spontaneous perforations of the sigmoid colon occur in patients with EDS. Conclusion: Surgery in patients with EDS is associated with a high risk of complications, which is why preoperative indications should be considered. Optimal therapy for these patients includes the awareness that EDS is a systemic disease involving fragility, bleeding and spontaneous perforations from almost all organ systems. Often, a nonsurgical approach can be the best choice for these patients, depending on the condition.